Why moving towards a strong decentralized federal state would be beneficial for the European Union - Vesa Kanniainen (EconPol Forum, 2024)
Russia's attack on Ukraine has revealed the need to reassess Europe's security. Currently, the European Union is a politically fragmented and divided union of member states, economically underperforming, with a defense capability that is insufficient without the support of the USA. The European Union should develop towards a stronger decentralized federation, but by restoring the principle of subsidiarity. When it comes to sharing political power, the Swiss model is more suitable for the European Union than the US model.
Keywords: 330